The role of MnO in Ni/MnO-Al2O3 catalysts for carbon dioxide reforming of methane - Seok, SH; Han, SH; Lee, JS (ELSEVIER, 2001)
Addition of manganese to Ni/Al2O3 improves the stability of the catalyst in CO2 reforming of methane. The role of manganese has been investigated particularly in view of the deposition of unreactive carbon on the catalyst surface. Results of XRD, XANES, TEM and hydrogen chemisorption indicate that the surface of nickel is partly covered ("decorated") by patches of MnOx. Manganese addition also promotes the adsorption of CO2 by forming a reactive carbonate species. Both of these effects appear responsible for the suppression of carbon deposition over Ni/MnO-Al2O3. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: SYNTHESIS GAS; SOLID-SOLUTION; NICKEL; DEPOSITION; PERFORMANCE; SUPPORT; RHODIUM; OXIDES; CH4